Analisis Pengaruh Kinerja Bank Umum Syariah Dengan Pendekatan Sharia Conformity And Profitability (SCnP) Terhadap Pertumbuhan Dana Pihak Ketiga - Harahap, Rahmat Daim; Imsar; Ramadhani, Hafiz Aryo (Balance : Jurnal Akuntansi dan Manajemen, 2022)
This research is motivated by the movement of Third Party Fund growth which fluctuates from year to year both in terms of nominal and amount in Islamic commercial banks. Therefore, it is necessary to measure the performance of Islamic banks using the concept of a combination of the sharia side and the conventional side. This study aims to determine the effect of Islamic income, profit sharing, return on assets, and net profit margin on the growth of third-party funds for Islamic commercial banks from 2016-to 2020. The research method uses a quantitative approach with data sources obtained from the official website of the Financial Services Authority, Islamic Banking Statistics, and the official website of each Islamic commercial bank. The analysis technique used is the multiple linear regression test. The results of this study indicate that the variables of Sharia Income, Profit Sharing, ROA, and NPM simultaneously have a positive and significant influence on the growth of BUS Third Party Funds. then partially this also applies. it can be stated that the measurement of the performance of Islamic commercial banks using the principles of sharia conformity and profitability can be used as a basis for sharia bank stakeholders to take future steps.